Analysis of the effect of phloroglucinol on pregnancy outcomes involving frozen embryo transfers in patients with endometriosis: A retrospective case-control study - Pang, Wen-Juan; Feng, Xu; Wang, Xiang; Wang, Liang; Sun, Ning-Xia (Frontiers in Surgery, 2023)
Objective: This study investigated the effect of phloroglucinol on frozen embryo transfer in patients with endometriosis. Methods: The data of patients with endometriosis who underwent a frozen embryo transfer in Shanghai Changzheng Hospital from August 2018 to August 2021, comprising a total of 453 cycles, were retrospectively analyzed. The patients for whom phloroglucinol was included over 217 cycles were administered 40 mg phloroglucinol via intramuscular injection starting on the day of endometrial transformation, then once daily up to day 7 after the embryo transfer. Those for whom phloroglucinol was not administered over 236 cycles were used as the control group. The age of 35 years was used as a boundary in this study to observe the pregnancy outcomes of patients in the two different age groups. Results: The biochemical pregnancy rate (63.13% vs. 51.27%), embryo implantation rate (44.64% vs. 33.60%), clinical pregnancy rate (59.64% vs. 48.30%), and live birth rate (52.99% vs. 36.86%) after the administration of phloroglucinol were higher than for patients in the control group, and the early abortion rate (7.75% vs. 20.18%) was also lower. The differences were statistically significant (P < 0.05). In particular, in the age group <35 years old, the embryo implantation rate (51.81% vs. 39.38%), clinical pregnancy rate (69.34% vs. 57.55%), and the live birth rate (63.50% vs. 44.60%) after phloroglucinol intervention rose significantly, and the abortion rate dropped (6.32% vs. 17.5%), indicating a statistically significant difference (P < 0.05). However, pregnancy outcomes showed no difference in the age group ≥35 years old (P > 0.05). Conclusion: Continuous low-dose phloroglucinol pretreatment before and after frozen embryo transfer can improve both the clinical pregnancy and live birth rates and reduce the risk of abortion in younger infertile patients with endometriosis.